The linear and non-linear magnetic response of a tri-uranium single molecule magnet. (27th January 2017) - Shivaram, B S; Colineau, E; Griveau, J; Kumar, P; Celli, V
Abstract: We report here low temperature magnetization isotherms for the single molecule magnet, (UO2 -L)3 . By analyzing the low temperature magnetization in terms of M = χ 1 B + χ 3 B 3 we extract the linear susceptibility χ 1 and the leading order nonlinear susceptibility χ 3 . We find that χ 1 exhibits a peak at a temperature of T 1 = 10.4 K with χ 3 also exhibiting a peak but at a reduced temperature T 3 = 5 K. At the lowest temperatures the isotherms exhibit a critical field B c = 11.5 T marked by a clear point of inflection. A minimal Hamiltonian employing S = 1 (pseudo) spins with only a single energy scale (successfully used to model the behavior of bulk f-electron metamagnets) is shown to provide a good description of the observed linear scaling between T 1, T 3 and B c . We further show that a Heisenberg Hamiltonian previously employed by Carretta et al (2013 J. Phys.: Condens. Matter 25 486001) to model this single molecule magnet gives formulas for the angle averaged susceptibilities (in the Ising limit) very similar to those of the minimal model.